2001
DOI: 10.1029/2000gl012340
|View full text |Cite
|
Sign up to set email alerts
|

Global observations of proton and electron auroras in a substorm

Abstract: Abstract. This is the first report of a substorm observed by the IMAGE FUV instruments permitting global observations of electron and proton produced auroras. On the 28 th of June 2000 at 1956 UT in the pre-substorm phase at early evening local time the proton aurora was equatorward of the electron precipitation and near midnight they were collocated. There was bright electron and proton aurora in the post midday afternoon side. The sudden brightening of the aurora at substorm onset near midnight is seen in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 15 publications
2
34
0
Order By: Relevance
“…The FAST satellite passes through this newly developed surge region at 1117, or 6 minutes after the start of the surge. Some substorm features described by Mende et al [2001] can be seen in this event. For example, the temporal and spatial coincidence of the initial proton intensification and poleward expansion with the electron auroras (not shown).…”
Section: Data Presentationmentioning
confidence: 63%
“…The FAST satellite passes through this newly developed surge region at 1117, or 6 minutes after the start of the surge. Some substorm features described by Mende et al [2001] can be seen in this event. For example, the temporal and spatial coincidence of the initial proton intensification and poleward expansion with the electron auroras (not shown).…”
Section: Data Presentationmentioning
confidence: 63%
“…Consequently, the fractional proton contribution is minimum during the substorm most active phase. Mende et al [2001] showed the example of a substorm where the total electron precipitation suddenly increased one whole order of magnitude, while the protons increase only about 50%. The intensification of the precipitating electrons was relatively short‐lived (∼ 10 minutes) while the ENA enhancements, which are mostly indicative of the enhanced trapped particle population, are as long as an hour.…”
Section: Discussionmentioning
confidence: 99%
“…Higherenergetic particles with the large pitch angles can also give a contribution to the maximum of the hydrogen line profile, but this contribution is much weaker because of the decrease in excitation efficiency at the larger energies (>20 keV). Besides, in some papers, the dependence of the efficiency of hydrogen emission excitation on initial proton energy is ignored (for example, Mende et al (2001)). …”
Section: Modelling Of the Degradation Of The Proton-h Atom Fluxmentioning
confidence: 99%
“…Using global observations of electron and proton produced auroras observed by IMAGE satellite FUV instruments, Mende et al (2001) concluded that the peak intensity of the proton aurora did not change substantially during substorms. They found that the initial brightening of the substorm was embedded in proton precipitation, which coincides with the results of Samson et al (1992).…”
Section: Introductionmentioning
confidence: 99%